Ativismo literário - Ecotopia - Matias, Marcus Vinicius (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
The worsening of environmental problems is already configured as one of the characteristics that define 21st century. Movements that warn us about the development of climate changes, the pollution of oceans with tons of plastics and the abuse of predatory consumption societies are added on recurrent issues of global warming and inappropriate land use. I propose to discuss how these movements of awareness and dissemination of critical thinking about environmental problems are engendered through literary activism and utopian thinking. For this, I approach concepts such as sustainability and resilience, from the perspective of Phillips (2017), and also the proposal of Ecocriticism, discussed by Buell, Heise, and Thornber (2011), and Garrard (2004). As for literary perspective, works like MaddAddam, by Atwood, and Ecotopia, by Callenbach, are some of the examples that illustrate this analysis. I therefore seek to discuss how literary activism presents itself in the face of environmental problems.